Learning Model-Based Digital Character Education In Al-Hikmah Boarding School Batu - Arsyadana, Addin; Ahmadi, Rizqa (Didaktika Religia, 2019)
This study seeks to explain a learning model of education in Al-Hikmah Islamic Boarding School, Batu. A very rare model of learning found in other educational institutions. In addition to rare, this model is a breakthrough solution-based on a variety of educational inequality that is often difficult to formulate between character education and digital-based learning. The significance of this study lies in the new models that are developed concerning the national education curriculum and meet the standards of 2013. This study used a qualitative research approach that is approached with a descriptive analysis. Retrieving data using interview and observation techniques, the results of these data in the process were analyzed using inductive analysis techniques. In the final stage, then the data is authenticated using the method of triangulation techniques. After doing research, it was found several important findings as to the end of the study. Digital-based character education models essentially have three interrelated aspects; methodology, habituation, and control. The methodology used is the First, the method of identification problems. Second, the method of movie reviews. Third, the method of making the story of Arabic and English Fourth, the preparation method illustrated stories through the application. While habituation performed on all subjects internalize sector. In addition to the internalization, there is also a character-building activity taken us turÄth reference source that is Adab wa Taâ€™lÄ«m al-Mutaâ€˜allim. The latter is a control that is by silaturrahmi guardian to students and information from the public.